ARGON DIFFUSION AND SOLUBILITY IN SILICIC GLASSES EXPOSED TO AN AR-HE GAS MIXTURE - Draper D.S.; Carroll M.R. (My University, 1995)
We have determined argon solubility and diffusivity in SiO2, NaAlSi3O8, and rhyolitic composition glasses exposed to an equimolar Ar gas mixture at 1225-2500 bars and 500-850°C. The diffusivity results from the mixedAr experiments are almost identical to those from experiments with pure Ar. Activation energies for diffusion (Ea, kJ mol-1, +/- 1σ uncertainties) are, for silica, 110.9 +/- 2.1 (He mix) vs. 100.8 +/- 5.4 (pure-Ar); for albite, 157.3 +/- 3.8 (He mix) vs. 137.2 +/- 6.3 (pure-Ar); and for rhyolite, 161.9 +/- 1.7 (He mix) vs. 144.3 +/- 6.3 (pure-Ar). Argon solubilities determined from these experiments show slight negative deviations from Henry's Law (fArXAr = K, the Henry's Law constant), as observed in pure-Ar experiments at Ar fugacities greater than about 1500 bars. The predominant effect of He on Ar solubility in the mixed-gas experiments is one of dilution of Ar activity in the gas phase; solubilities in mixed-gas experiments are similar to those of pure-Ar experiments performed at equivalent Ar fugacities. These observations, combined with measured noble gas concentrations in natural glasses, suggest that there should be no significant interactions between different dissolved noble gas atoms in natural melts.